Curcumin Ameliorates Cardiac Fibrosis by Regulating Macrophage-Fibroblast Crosstalk via IL18-P-SMAD2/3 Signaling Pathway Inhibition - Zhao, Jing; Chen, Yongjian; Chen, Qiming; Hong, Tingting; Zhong, Zhiwei; He, Junhua; Ni, Cheng (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: Curcumin is a bright yellow chemical produced by plants of the Curcuma longa species. Chemically, curcumin is a diarylheptanoid, belonging to the group of curcuminoids. The therapeutic potential of curcumin has been widely investigated, including its utilization in various of cardiovascular diseases. However, its effect in cardiac remodeling post myocardial infarction and underlying mechanism remains to be uncover. Aim: To evaluate the therapeutic effect and underlying mechanism of curcumin on cardiac fibrosis after myocardial infarction via macrophage-fibroblast crosstalk. Methods: Male C57BL/6 (C57) mice were subjected to left anterior descending coronary artery ligation to establish myocardial infarction and intragastrically fed vehicle or curcumin (50 mg/kg or 100 mg/kg) for 4 weeks. In parallel, neonatal rat cardiac fibroblasts were isolated and co-cultured with liposaccharide (LPS− or LPS+) curcumin-treated macrophages, followed by TGF-β stimulation for 24 h. Cardiac function was determined by 2-dimensional echocardiography, and cardiac fibrosis was measured by picrosirius red staining. Apoptosis of macrophages was investigated by flow cytometry; all pro-fibrotic protein expression (EDA-Fibronectin, Periostin, Vimentin, and α-SMA) as well as TGF-βR1 downstream signaling activation reflected by phosphorylated SMAD2/3 (p-SMAD2 and p-SMAD3) were demonstrated by western blotting. Results: Curcumin significantly ameliorated the inflammation process subsequent to myocardial infarction, reflected by decreased expression of CD68+ and CD3+ cells, accompanied by dramatically improved cardiac function compared with the placebo group. In addition, cardiac fibrosis is inhibited by curcumin administration. Interestingly, no significant reduction in fibrotic gene expression was observed when isolated cardiac fibroblasts were directly treated with curcumin in vitro; however, pro-fibrotic protein expression was significantly attenuated in CF, which was co-cultured with LPS-stimulated macrophages under curcumin treatment compared with the placebo group. Mechanistically, we discovered that curcumin significantly downregulated pro-inflammatory cytokines in macrophages, which in turn inhibited IL18 expression in co-cultured cardiac fibroblasts using bulk RNA sequencing, and the TGF-β1-p-SMAD2/3 signaling network was also discovered as the eventual target downstream of IL18 in curcumin-mediated anti-fibrosis signaling. Conclusion: Curcumin improves cardiac function and reduces cardiac fibrosis after myocardial infarction. This effect is mediated by the inhibition of macrophage-fibroblast crosstalk in the acute phase post-MI and retrained activation of IL18-TGFβ1-p-SMAD2/3 signaling in cardiac fibroblasts.